Payment for ecosystem services initiatives: panel discussion #3 - Sprague, Eric, speaker; Gartner, Todd, speaker; Corbin, Chris, speaker; Lynch, Sarah, speaker; Widmark, Derrick, speaker; Toombs, Ted, speaker; Dickinson, T. Wright, speaker; Flynn, Patrick, moderator (Colorado State University. Libraries, 2011)
In this video are representatives from eight different ecosystem market initiatives around the country briefly describing their projects. Moderated by Patrick Flynn from the Center for Collaborative Conservation. The representatives are Eric Sprague - Bay Bank, Todd Gartner - World Resources Institute, Chris Corbin - Lotic Water Marketing, Sarah Lynch - World Wildlife Fund, Derrick Widmark - Diablo Trust, Ted Toombs - Environmental Defense Fund, and T. Wright Dickinson - Partners for Western Conservation.
Presented at a workshop entitled "Stepping toward the future: marketing environmental services on working lands of the American West" on May 23-25, 2011 on the CSU campus. The purpose of the workshop was to bring together regional and national leaders from the ranching community, conservation organizations, businesses, universities, and government to explore ways to catalyze the development of payments for ecosystem services in Colorado and across the American West. Over 80 participants attended the conference, which also highlighted the CCC's work to create an ecosystem marketplace in northern Colorado.
Includes recorded video presentation.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: ecosystem services; environmental markets